2021
DOI: 10.1590/0037-8682-0375-2020
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in leprosy and drug resistance assessment in a tertiary hospital of the state of Espírito Santo, Brazil

Abstract: Introduction: Leprosy recurrence is the reappearance of the disease after treatment with current schemes and discharged for cure and may have variable incubation periods. Methods: This is a descriptive observational study of leprosy recurrence in Espírito Santo diagnosed between January 2018 and January 2020. Results: One hundred and ninety-two cases were available, of which 30 were diagnosed with leprosy recurrence. Conclusions: In 25 cases, the incubation period was 5-15 years after the first treatment, favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Gonçalves et al (2019) [63] state that relapses greater than 15 years are commonly experienced by those who are continuously exposed to the bacillus. Chagas et al (2021) [55], ratify this result, as 40% of relapses in their patients were due to household contact. Lobo et al (1992) [64] advise about their finding of 24% of relapses detected in the first 18 months, as they may be late reversal reactions.…”
Section: Relapsementioning
confidence: 56%
See 2 more Smart Citations
“…Gonçalves et al (2019) [63] state that relapses greater than 15 years are commonly experienced by those who are continuously exposed to the bacillus. Chagas et al (2021) [55], ratify this result, as 40% of relapses in their patients were due to household contact. Lobo et al (1992) [64] advise about their finding of 24% of relapses detected in the first 18 months, as they may be late reversal reactions.…”
Section: Relapsementioning
confidence: 56%
“…In surveys carried out in specialized centers for leprosy, the results showed that the percentage of relapse cases in Northern India was 61% [51]; in Northern Italy in refugees/migrants, it was 35% [52] and in Midwest Brazil, it was 10 % [53] Studies carried out in two Brazilian states revealed that the relapse of the disease is more frequent in multibacillary patients [54,55]. Already under study in Colombia, the virchowian clinical form is specified, which is classified as multibacillary, with a four-times greater probability of the disease occurring compared to other clinical forms [31].…”
Section: Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…The main findings from the studies indicated that the relapse occurrence time after the initial PCT treatment is equal to or greater than 5 years after clinical cure, with higher prevalence of patients treated for MB 26,27,28,29 . Complementary findings from the cohort studies revealed that relapse cases were more prevalent among cases with positive bacilloscopy when compared to those with negative bacilloscopy in the initial treatment 13,14,15,30,31,32,33,34,35,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Characteristics Of the Population And Clinical Aspects Accor...mentioning
confidence: 99%
“…This fact indicates the need for clinical criteria to guide the selection of alternative treatments for suspected cases of resistance. 20 Before initiating an alternative treatment, clinical providers must first thoroughly exclude the possibility of reinfection and ensure that adherence to the standard treatment was adequate. 21,22 Therefore, repeated evaluation of household contacts and a detailed investigation of the patient's clinical history are essential before any alternative treatment is considered for patients with inconclusive tests for antimicrobial resistance.…”
Section: Gene Sequencingmentioning
confidence: 99%